2004
DOI: 10.2337/diabetes.53.8.2067
|View full text |Cite
|
Sign up to set email alerts
|

Partial Gene Deletion of Endothelial Nitric Oxide Synthase Predisposes to Exaggerated High-Fat Diet—Induced Insulin Resistance and Arterial Hypertension

Abstract: Nitric oxide (NO) plays a major role in the regulation of cardiovascular and metabolic homeostasis, as evidenced by insulin resistance and arterial hypertension in endothelial NO synthase (eNOS) null mice. Extrapolation of these findings to humans is difficult, however, because eNOS gene deficiency has not been reported. eNOS gene polymorphism and impaired NO synthesis, however, have been reported in several cardiovascular disease states and could predispose to insulin resistance. High-fat diet induces insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 33 publications
(14 reference statements)
6
84
0
1
Order By: Relevance
“…For example, in skeletal muscle tissue, the endothelial form of NO synthase (eNOS) plays an important role in the intrinsic regulation of insulin-stimulated glucose uptake in vitro and in the regulation of blood flow and substrate delivery during hyperinsulinemic clamp studies in vivo (3). In line with this concept, we and others have shown that in mice, the ablation of the eNOS gene leads to hypertension and insulin resistance (3)(4)(5)(6) and that insulin-regulated eNOS expression is an important feature of diabetes (5,6).…”
supporting
confidence: 55%
“…For example, in skeletal muscle tissue, the endothelial form of NO synthase (eNOS) plays an important role in the intrinsic regulation of insulin-stimulated glucose uptake in vitro and in the regulation of blood flow and substrate delivery during hyperinsulinemic clamp studies in vivo (3). In line with this concept, we and others have shown that in mice, the ablation of the eNOS gene leads to hypertension and insulin resistance (3)(4)(5)(6) and that insulin-regulated eNOS expression is an important feature of diabetes (5,6).…”
supporting
confidence: 55%
“…Therefore, investigation into whether certain maternal behaviors or components of breast milk are responsible is warranted. The potential modulating role of postnatal nutrition in our model is supported by the findings of Cook et al 17 These investigators found that NOS3 +/− mice fed a normal diet had normal insulin sensitivity and were normotensive. However, when fed a high-fat diet over an 8-week period, they developed exaggerated arterial hypertension and had fasting hyperinsulinemia and a 35% lower insulinstimulated glucose utilization than control mice.…”
Section: Commentsupporting
confidence: 73%
“…NO, described initially as an endothelial cell-derived relaxing factor, is an important regulatory molecule in the cardiovascular system, and reduced NO levels are associated with hypertension and insulin resistance (35)(36)(37). Urate can react directly with NO under aerobic conditions to generate an unstable nitrosated uric acid product that can transfer NO to other molecules such as glutathione (ref.…”
Section: Uric Acid: Antioxidant or Pro-oxidant?mentioning
confidence: 99%